When It Comes to Complex NPs, Not All Preschoolers Agree. Issue 4 (2nd October 2019) - Lorimor, Heidi; Stephens-Hecker, Nola; Miller, Carol
ABSTRACT: Using an oral sentence production task, we investigated how preschoolers (N = 28) produce agreement with complex noun phrases and compared their performance to college students (N = 32) to determine whether preschoolers produce agreement patterns that are qualitatively similar to adults'. We also conducted corpus analyses to investigate relevant input to preschoolers and found very few sentences in which the verb expressed unambiguous agreement with the head noun of a complex noun phrase. In the oral production task, preschoolers made more errors when the head and local nouns had different number specifications than when the nouns were both singular or plural. Response bias calculations indicated that preschoolers often produced one type of agreement (singular or plural) when the subject head and local nouns differed in number. College students were more accurate overall, and a comparison between preschoolers and college students revealed qualitative differences in agreement patterns between the two groups.